Mitigation of the Potential Socio-Economic Impact of Marine Sediment Utilization on Housewives in Bintan Regency through Collaborative-Based Counseling Guidance Services - Putri, Nanda Gustia; Marpaung, Junierissa; Ramdani, Ramdani; Yanizon, Ahmad; Darunkan, Thammasin; Soeboer, Deni Achmad (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to analyze the perception of coastal women in Bintan towards marine sediment cleaning and utilization activities and identify the ecological and socio-economic impacts caused, as well as formulate the need for a mitigation model based on Collaborative Counseling Guidance. This study uses a qualitative descriptive approach enriched by quantitative data through the distribution of questionnaires to 35 coastal mothers who were selected purposively. Data were obtained through field observations, structured and semi-structured interviews, and questionnaires developed based on ecological, socio-economic, and psychosocial impact indicators. Data analysis is carried out through descriptive statistics and thematic analysis and enriched with integrative conceptual analysis to connect empirical findings with theoretical frameworks. The results of the study show that sedimentation activities cause an increase in water turbidity and a decrease in catches, which has a direct impact on the economic instability of fishery families. Despite this, coastal mothers show high adaptive resilience through adjustment of household economic strategies and readiness to seek alternative sources of income. Overall, the findings of the study confirm the need for a Collaborative BK model that is able to provide psychosocial support and economic empowerment as a multidimensional mitigation strategy for coastal families in Bintan.